Christian sports coaches and servant leadership. Issue 2 (April 2021) - Vinson, Don; Parker, Andrew
The world of competitive sport can present a challenging environment for Christian athletes and coaches. The culture of competitive sport, and particularly the attitude to winning, can cause athletes and coaches to question how their Christian faith should shape participation and/or whether they should participate at all. Few empirical studies have explored how Christian coaches frame their practice to align with their faith and reconcile the potential contradictions and challenges of coaching within competitive sporting environments. That said, there has been a recent increase in the number of studies exploring the potential relationship between sports coaching and the concept of servant leadership – a framework which is commensurate with a Christian world view. The aim of this paper is to contribute to these debates by presenting empirical evidence to explore the philosophies, intended practices and sociocultural factors influencing how Christian coaches sought to lead in competitive sporting environments. One hundred and ten coaches (female = 24, male = 86) completed an online qualitative questionnaire which explored their beliefs about leadership and coaching practice. This paper considers the ways in which Christian coaches' might seek to frame their leadership behaviours within the context of competitive sport and how their approaches might align, or otherwise, with the theoretical tenets of servant leadership.